Developing Listening Materials for the Tenth Graders of Islamic Senior High School - Alimin, Alimin (Universitas PGRI Adi Buana Surabaya, 2019)
This study is intended to develop listening materials. The research problem was “What is the appropriate listening material for the tenth graders of Islamic Senior High School of MA Ma’arif 7 Banjarwati. The study was designed in the form of Research and Development (R & D). The steps were need analysis, developing listening materials, expert and teachers’ validation, revision, try out, and final product. In collecting the data, several instruments were used. They are try-out, questionnaire, observation, and field notes. After the materials have been developed and validated by the expert and teacher, then it is tried out. Ten students were involved the try out. After the try out, the students stated their opinion. For the attractiveness, clarity of the recording, speed of delivery, vocabulary usage, and difficulty. Most the students stated that the materials were very good. For the result of the try out, the students made the most mistakes on ticking true or false activities. The steps of the research are need analysis, developing materials, expert and teachers’ validation, revision, try out and the final product. The product of this study is teacher’s book, student’s worksheet, and the listening materials. The materials are compiled in the form of CD. They are the language, length, content, style, and speed of delivery, the style of delivery and the quality of the recording. The materials are suitable with the students’ need, interest, and level of students’ ability in English. Listening activities can motivate students’ interest in learning English. Listening materials can give teachers a lot of input to be better in preparing listening activities